How to conceive of science for the benefit of society: prospects of responsible research and innovation. - Carrier, Martin (Synthese)
Responsible research and innovation (RRI) features the dialog of science "with society," and research performed "for society," i.e., for the benefit of the people. I focus on this latter, outcome-oriented notion of RRI and discuss two kinds of problems. The first one concerns options to anticipate the future course of science and technology. Such foresight knowledge seems necessary for subjecting research to demands of social and moral responsibility. However, predicting science and technology is widely considered impossible. The second problem concerns moral evaluation. The benefit or harm produced by certain research and innovation achievements is often hard to estimate. Against this background of uncertainty in factual and moral assessment, I explore opportunities left for RRI. First, RRI should contribute to maintaining a wide range of approaches. Second, judgments about RRI should draw on zones of convergence among the variety of research approaches pursued. Third, decisions about implementing a technology should be revisable. Fourth, the more specific inclusion of demands from society should be reserved to technology development. Fifth, in many respects, the social compatibility of a new technology is due rather to the social context than the inherent features of the product. Favorable circumstances are transparency, representation of all relevant parties, and procedural fairness. As a result, some of the benefits and detriments of research and innovation can be identified without detailed knowledge of future findings.